Short-term in vitro effects of bisphenol A activity on phenotype and function of peripheral blood immune system cells. (December 2017) - Zbucka-Kretowska, M.; Poplawska, I.; Kretowska, A.; Moniuszko, M.; Grubczak, K.
Abstract: Bisphenol A (BPA) is a phenolic compound being constituent of numerous everyday-used products. Additionally, good absorption through skin and gastrointestinal tract is an unquestionable evidence for high risk of BPA exposure and its possible influence on health. Effects of BPA action on cells and tissues are associated with its structural and functional similarities to steroid hormones. Here we investigated whether BPA could possibly influence immune cells through steroid receptors present on majority of these cells. In in vitro experiments with 200 nM and 1000 nM BPA concentrations we found that high levels affect activation of lymphocytes through increased CD25 expression, with no changes in functional response based on IFN-gamma production. We demonstrated that BPA influence not only phenotype of monocytes with increased frequency of CD14++CD16- subtypes, but also activation inhibition with decline of HLADR expression within monocytes. Similarly to lymphocytes, no changes were observed in context of monocytes function in BPA-exposed cells. Our study revealed that BPA actions are also associated with its direct role in modulation of immune system cells. We presume that further experiments would allow establishing connection between presented data and increased risk of cancer and metabolic diseases in subject exposed to bisphenol A. Highlights: High doses of BPA applied did not affect lymphocytes' and monocytes' viability. BPA induced changes in phenotype and activation status of immune cells. BPA activity did not influence cytokine production by lymphocytes and monocytes. Phagocytic activity of monocytes was not affected by BPA stimulation.